PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) PADA MATERI ARITMATIKA SOSIAL - SARTIKA . (Departemen Matematika, 2021)
This study discusses the process of developing student worksheets with RME approach on social arithmetic. This uses the Plomp development model which consists of three stages is Preliminary Research and Prototyping Phase. The prototyping phase is consisting of prototype 1 and prototype 2. In prototype 1, self-evaluation and expert review to see the validity of the developed student worksheets. In prototype 2, a One-to-One Evaluation was stage is carried out to measure the practicality of the student worksheets being developed. Validity is measured based on a validity questionnaire filled out by three validators and practicality is measured based on a practicality questionnaire filled out by three respondents.Based on the results of the development of student worksheets based on the RME approach, a valid and practical student worksheets was obtained. The results of the validity data analysis reached a value of 89.58% with a very valid category. The results of practical data analysis of student worksheets reached a value of 87.5% including the very practical category. So, it can be concluded that student worksheets based on the realistic mathematic education approach on social arithmetic material has met the criteria of validity and practicality. Keywords— Development Research, Student Worksheet, RME